Analisis Faktor – Faktor Yang Memengaruhi Harga Daging Sapi di Jawa Barat (Jurnal Agribisnis Indonesia, 2023)
West Java has a consumption level of beef above the national average consumption level. Beef is an essential commodity for the residents and the economic system of West Java Province. However, the price of beef in West Java is unstable. In May 2021, beef became the second biggest contributor to inflation in West Java. High inflation has had a negative impact on economic actors, so efforts to stabilize beef commodity prices is important. The purpose of this research is to analyze the factors that influence the price of beef in West Java. This research applies a time series data of 2003-2020 and the error correction model method. The results of the study showed that the long-term variable price of chicken meat and international beef prices have a positive effect on the price of beef in West Java. Meanwhile, in the short term, the beef cattle population had a negative effect and the chicken meat price had a positive effect on beef prices in West Java. The results of this study indicate that a stable beef price can be achieved by increasing the population of beef cattle, especially culled cows and ready-to-slaughter bulls. In addition, the research results also show that chicken meat is a substitute commodity for beef, so to meet the public's need for animal protein, it is also important to stabilize the price of chicken meat. Stabilization of chicken meat and beef prices should be pursued to go hand in hand.